Methodology for assessing the influence of external and internal factors on the development of the digital economy - Verkhoglyadova, N. I.; Верхоглядова, Н. І.; Kononova, I. V.; Кононова, І. В.; Morozova, Ye. P.; Морозова, Є. П.; Brovko, Larisa; Бровко, Лариса Іванівна; Ostapenko, T. M.; Остапенко, Т. М. (Національний гірничий університет, 2023)
Purpose. To develop a mathematical model and propose an algorithm for analyzing and evaluating the impact on the digital economy and forming the method for choosing the factors of the external and internal impact which require institutional management measures. Methodology. Special and general methods of scientific knowledge are used: mathematical methods – for developing a model for assessing the effects on the digital economy and choosing institutional management measures; methods of analytical research – to distinguish groups of factors; the method of analysis and synthesis – when determining the most important factors and groups of influence and developing a management algorithm. Findings. Factors influencing the directions of investment in digital technologies for mass and corporate consumers and a significant difference in the amount of financing according to them have been identified. The possibility of a decrease in the level of competitiveness of the country due to the inadequacy of investing in digital technologies for the corporate sector is indicated. Management actions to increase investment in digital technologies for the corporate sector are recommended. Originality. The mathematical model and algorithm have been developed for the analysis and assessment of impacts on the digital economy and the formation of a method for selecting impact factors that require management measures. Using a mathematical model, the area of investing in the development of the digital economy was analyzed and management proposals for this area were developed. Practical value. The developed mathematical model for the analysis and assessment of impacts on the digital economy and the algorithm for monitoring, analysis and management of impacts can be implemented for scientific and practical purposes. призначення. Розробити математичну модель та запропонувати алгоритм аналізу та оцінки впливу на цифрову економіку та сформувати методику вибору факторів зовнішнього та внутрішнього впливу, які потребують інституційних заходів управління. Методологія. Використовуються спеціальні та загальні методи наукового пізнання: математичні методи – для розробки моделі оцінки впливу на цифрову економіку та вибору заходів інституційного управління; методи аналітичного дослідження – для виділення груп факторів; метод аналізу та синтезу – при визначенні найважливіших факторів і груп впливу та розробці алгоритму управління. Висновки. Визначено фактори, що впливають на напрями інвестування в цифрові технології для масових і корпоративних споживачів та суттєву різницю в обсягах фінансування відповідно до них. Вказано на можливість зниження рівня конкурентоспроможності країни через неадекватність інвестицій у цифрові технології для корпоративного сектору. Рекомендовано дії керівництва щодо збільшення інвестицій у цифрові технології для корпоративного сектору. Оригінальність. Розроблено математичну модель та алгоритм для аналізу та оцінки впливів на цифрову економіку та формування методики вибору факторів впливу, що потребують управлінських заходів. За допомогою математичної моделі проаналізовано сферу інвестування у розвиток цифрової економіки та розроблено управлінські пропозиції для цієї сфери. Практична цінність. Розроблена математична модель для аналізу та оцінки впливів на цифрову економіку та алгоритм моніторингу, аналізу та управління впливами можуть бути реалізовані для наукових і практичних цілей.
Методологія оцінки впливу зовнішніх і внутрішніх факторів на розвиток цифрової економіки
Keywords: methodology; методологія; digital economy; цифрова економіка; influence factors; фактори впливу; external and internal influence; зовнішній та внутрішній вплив; algorithm; алгоритм